THE INFLUENCE OF HEALTH EDUCATION ON THE IMPACT OF PARENTAL VERBAL VIOLENCE ON PRESCHOOL CHILDREN ON PARENTS' KNOWLEDGE AND ATTITUDES IN TK KANIGORO KRAS - Nurhidayah, Nurhidayah; Khoirudin, M.; Dewi, Dita Kirana (Jurnal Education and Development, 2026)
Preschool children are an age group at a critical stage of development where life experiences, both positive and negative, affect their emotions, behavior, and personality in the future. However, parents are often unaware of verbal violence committed against children. The purpose of this study was to determine how violence education affects parents' knowledge and attitudes about parental verbal violence against preschool children. This research design was Quasy Experimental with a One-group pre & post test design approach. The study population was all parents at Kanigoro Kras Kindergarten, totaling 32 parents. With a sample of 32 respondents, taken using the total sampling technique. The independent variable was Health Education, the dependent variable was knowledge and attitude. Data collection used a questionnaire. Data were expressed on an ordinal scale and analyzed using the Wilcoxon Test (α: 0.05). The results of the study showed that 31 respondents had good knowledge before Health Education to 32 respondents after Health Education. The results of the Wilcoxon Test Analysis obtained a significant value of P-Value = 0.02 <α = 0.05, H1 was accepted. Before and after Health Education, 32 respondents had a good attitude, with the results of the Wilcoxon Test analysis obtained a significant value of P-Value = 0.000 <α= 0.05, H1 is accepted. In conclusion, there is an influence of Health Education on the impact of verbal violence by parents on preschool children on parental knowledge and attitudes. It is hoped that Health Education can improve parental knowledge and attitudes about the impact of verbal violence on preschool children.